2014
DOI: 10.1016/j.jcmg.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of RV Function Before and After Lung Transplantation

Abstract: Alterations of RV function and pulmonary artery pressure normalize, and post-transplantation RV function may provide prognostic data in patients after lung transplantation. Our study is based on a highly and retrospectively selected group. We believe that larger prospective studies are warranted to confirm this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…We have previously shown that HF initiated by tachycardia-induced cardiomyopathy in dogs leads to increased LA size. [ 24 ] Thus, the absence of further LA dilatation during 6 months of AF maintenance seems puzzling. A likely explanation is that the dramatic increase in LA size and atrial fibrosis induced by HF [ 25 ] masks any further dilatation following AF induction.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HF initiated by tachycardia-induced cardiomyopathy in dogs leads to increased LA size. [ 24 ] Thus, the absence of further LA dilatation during 6 months of AF maintenance seems puzzling. A likely explanation is that the dramatic increase in LA size and atrial fibrosis induced by HF [ 25 ] masks any further dilatation following AF induction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because of the close anatomical relationship between the two ventricles and the interdependence of RV performance and LV filling, alteration of RV function may affect LV function [ 28 ]. RV function has therefore been shown to be an important clinical and survival determinant in various human cardiac and respiratory diseases [ 5 13 20 27 29 ]. Consequently, reliable non-invasive techniques allowing the detection of RV dysfunction are of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, echocardiography is preferred as the initial screening modality for diagnosis of PH. A few studies have used echocardiography to investigate mortality among lung transplant recipients with poor RV function (15,16,21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that PH, when confirmed by cardiac catheterization, is an independent predictive factor for survival after LTX (7,(10)(11)(12)(13). In addition, several studies have also analyzed post-LTX prognosis via echocardiography (14)(15)(16). However, almost all studies were exclusively designed for idiopathic pulmonary fibrosis (IPF) or other individual lung diseases.…”
Section: Introductionmentioning
confidence: 99%